Health Education Can Improve The Knowledge of Parents About Children's Dental Care. - Alfiani Rohmatulloh (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Many cases of tooth decay today are caused by a lack of parental knowledge about proper food selection and dental care for their children, especially children aged 4-6 years. This research method uses a descriptive exploratory approach by comparing mothers' knowledge about children's dental care. guardian of